Leadership in librarianship / Khasiah Zakaria - Zakaria, Khasiah (2010)
Some quarters may find that there is an “absence” of leadership in librarianship. Leadership is an integral part of any social system and is, therefore, always present. The absence, however, of a shared perception by members of a group about who its leaders are may indicate the absence of a common agenda. Leaders draw strength from their capability to clarify common group goals and purposes. A group that does not share these goals and purposes is hard pressed to share its perceptions of who is providing leadership. This article will be focusing on three main points; of what constitutes as leadership, its defined meaning in the context of librarianship, and why there is a need to project leadership in librarianship? The articles also will draw some examples from Academic Libraries in Malaysia.